Laminar entry region mixed convection heat transfer from an inclined rectangular fin array. Issue 6 (4th March 2020) - Roy, Krishna; Giri, Asis; Das, Biplab
Abstract : Purpose: The paper aims to investigate the influence of the angle of inclination on mixed convection heat transfer from rectangular plated shrouded fin array computationally. This study has got applications in the various thermal field such as cooling, solar thermal and so on. Design/methodology/approach: A computational study is made to evaluate the thermal performance in an inclined channel. Findings: Increase in clearance from 0.01 to 0.25 results in an increase of local Nusselt number by is as high as 15% near the exit. At a higher value of Gr with an increase in C * from 0.10, Nu is found to increase by 5.5%. Increase in Gr by 1.37 times results in enhancement of Nu by a maximum of 25-30%. Around 10% increase in overall Nu value is observed with an increase in inclination (i.e. from 30° to 60°). Practical implications: This study has got applications in the various thermal field such as cooling, solar thermal and so on. Originality/value: Entry region mixed convection in a shrouded inclined finned channel is performed.